Investigation on the Effect of Songs in Speaking Competency for EFL Young Learners in the Kindergarten Context - Susanti, Ni Kadek Ranny (Universitas Pendidikan Ganesha, 2025)
It is important to teach English for young learners. Teaching English for young learners are not the same as teaching the other level of learners. There are some challenges that must be faced by the teacher. The challenges are such as providing social interaction, improving cognitive development, creating safe and natural environment, and presenting learning context. Based on the previous studies, song is proven effective to improve the students’ motvation especially young learners’ motivation in learning English. This research has an aim to investigate the effect of using song to teach the students’ speaking competency. This is an experimental research in which the data will be presented in quantitative way or using numbers. The research was processed by independent t-test using SPSS. There were 40 samples. They were gained from the populations of TK Ganesa Putra 1 Sudimara in B level. To get the samples, cluster random sampling was used. The result was there is a significant difference on the students’ speaking competency. It was proven by the result of sig. (p = 0,000). From the result, it is suggested to use song as a media to teach the students’ English for improving the speaking competency.